A Spatial–Descriptive Paradigm of Non-Food Delivery-Based Enterprises: An Emphasis on Challenges and Opportunities - Crugie Boy A. Vitobina; Shane M. Dumagat; Cyrene Joy P. Santillan; Bryan S. Maglaque (Garuda Prestasi Nusantara Consulting, 2023)
The COVID-19 pandemic caused so many challenges that business owners were forced to stretch their strategies to survive and sustain their operations. Hence, the researchers aimed to determine and analyze the challenges and opportunities of non-food delivery-based enterprises amidst the pandemic. The researchers purposively selected 70 non-food delivery-based enterprises. A spatial-descriptive design was used to process and interpret the study. Considerably, the findings of the study revealed that non-food delivery-based enterprises in the municipality of Tanza, Cavite, were mostly under sole proprietorship, with limited staff, a business capitalization range below Php 3,000,000, and newly opened businesses. The key challenges identified in the study were cash borrowing, resource management, maintaining a consistent customer experience, new marketing trends, and curfew hours. On the other hand, selling more products or services, improving customer feedback, investing in developing business opportunities, and using new technology to increase efficiency are key opportunities. The researchers recommend strengthening marketing strategies that focus on enabling mechanisms for financial sustainability, customer satisfaction, and flexibility in the pandemic-led market environment. Keywords: challenges, COVID-19 pandemic, delivery enterprises, descriptive research, opportunities